Penerapan Teknologi Silase Complete Feed Berbasis Legum dalam Upaya Peningkatan Produktivitas Penggemukan Sapi Potong di Desa Bongomeme - Syamsul Bahri; Sutrisno Hadi Purnomo; Haris Singgili (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Forage availability in Bongomeme Village is relatively abundant, particularly local legumes. However, their utilization as preserved feed remains limited. This community service program aimed to enhance the knowledge and skills of beef cattle farmers in utilizing legumes through the application of complete feed silage technology. The implementation consisted of socialization, technical training, field practice, and evaluation stages. A total of 30 farmers participated actively in all phases of the program. The results indicated a significant improvement in participants’ understanding of legume nutritional value and silage production techniques. Farmers successfully produced high-quality silage using locally available materials, and several have begun to adopt the technology independently. High enthusiasm and strong institutional support at the local level further strengthened the potential for program sustainability. This initiative demonstrates that the transfer of legume-based silage technology offers a practical and context-appropriate solution to sustainably improve beef cattle fattening productivity among small-scale farmers. Keywords: silage, complete feed, legumes, beef cattle, community service